(Table 1) Interstitial-water chemistry at DSDP Hole 61-462 - Joris M Gieskes; Jeff Johnson (PANGAEA, 1981)
Concentration gradients of Ca, Mg, K, Sr, and Li at Site 462, Leg 61, are linear with depth; large changes occur in the unsampled, low-porosity limestone-chert zone between 375 and 445 meters. Correlations between Ca and Mg are linear, but breaks occur in Ca-Sr and Ca-K correlations. These breaks imply release of strontium in the limestones (recrystallization of carbonate) and uptake of potassium (formation of authigenic K-feldspar?).
Supplement to: Gieskes, JM; Johnson, J (1981): Interstitial-water studies, Leg 61. In: Larson, RL; Schlanger, SO; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 61, 603-605, https://doi.org/10.2973/dsdp.proc.61.116.1981